Modification of the existing maximum residue level for acequinocyl in strawberries - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; Stefanie Nave; et al. (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Agro‐Kanesho Kabushiki Kaisha submitted a request to the competent national authority in Greece to modify the existing maximum residue level (MRL) for the active substance acequinocyl in strawberries. The data submitted in support of the request were found to be sufficient to derive an MRL proposal for strawberries based on the indoor GAP. Adequate analytical methods for enforcement are available to control the residues of acequinocyl in strawberries at the validated LOQ of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of acequinocyl according to the reported agricultural practice is unlikely to present a risk to consumer health.